Polemika Euzebiusza z Cezarei z Sossianusem Hieroklesem na temat porównania Apoloniusza z Tiany i Chrystusa jako reprezentantów kultury pogańskiej i chrześcijańskiej - Tondera, Adam (Vox Patrum, 2015)
In the period of the growing importance of Christianity the pagan culture put forward Apollonius of Tyana as its eminent representative and a rival of Christ. At the beginning of the “great persecution” of the Christians Sossianus Hierocles, a high official in the administration of Diocletian, published his anti-Christian tract called The Lover of Truth, in which he drew a formal comparison between Apollonius and Christ. This way he tried to exalt Apollonius and the authors of the stories about him and the followers of the pagan culture. On the other hand he wanted to humiliate Christ and his apostles and all the Christians. Eusebius of Caesarea, the Christian historian, wrote a treatise in answer, in which he submitted the imagine of Apollonius, used by Hierocles in his anti- Christian propaganda, to a critical examination. His historical and philosophical critique reverses the objections of the adversary and shows some elements of pagan culture, represented by Apollonius, which should pass away.